1999
DOI: 10.1016/s0006-3495(99)77151-1
|View full text |Cite
|
Sign up to set email alerts
|

Calponin Interaction with α-Actinin-Actin: Evidence for a Structural Role for Calponin

Abstract: The purpose of this study was to address the paradox of calponin localization with alpha-actinin and filamin, two proteins with tandem calponin homology (CH) domains, by determining the effect of these proteins on the binding of calponin to actin. The results show that actin can accommodate near-saturating concentrations of either calponin and alpha-actinin or calponin and filamin with little change or no change in ligand affinity. Little direct interaction occurred between alpha-actinin and calponin in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 52 publications
(65 reference statements)
0
31
1
1
Order By: Relevance
“…This apparent contradiction may result from a nonspeci c interaction between calponin and a -actinin. However, we and others (19) have not detected any direct interaction between isolated calponin and a -actinin. Although we cannot completely exclude the possibility that after binding to actin the calponin and a -actinin start to interact with each other, such an interaction seems rather improbable for explaining the unusually high stoichiometry of ABPs bound to actin.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This apparent contradiction may result from a nonspeci c interaction between calponin and a -actinin. However, we and others (19) have not detected any direct interaction between isolated calponin and a -actinin. Although we cannot completely exclude the possibility that after binding to actin the calponin and a -actinin start to interact with each other, such an interaction seems rather improbable for explaining the unusually high stoichiometry of ABPs bound to actin.…”
Section: Discussioncontrasting
confidence: 71%
“…However, in contrast to Leinweber et al (19), we found that under certain conditions a -actinin can partially displace calponin. This difference may be due to the fact that we polymerized G-actin in the presence of two ABPs, whereas Leinweber et al (19) titrated F-actin with ABPs. We found that the structure of the actin bundles formed in the presence of only one ABP differs from that formed in the presence of both (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This hypothesis is consistent with the previous observations that UNC-87 knock-out animals display distorted myofilaments (12,14). A structural role has also been postulated for CaP (10,28), which bundles filaments at low ionic strength (29). Thus, we hypothesize that the cytoskeleton-stabilizing function of CaP is contributed by the C-terminal repeats.…”
Section: Discussionmentioning
confidence: 60%
“…UNC-87 binding to actin was also unaffected by saturating concentrations of either ␣-actinin or filamin, indicating the occupation of nonoverlapping sites on the actin filament. In support of this Chalovich and colleagues (28) reported that ␣-actinin, filamin, and calponin show only little displacement and are capable of binding the actin filament simultaneously in almost stoichiometrical amounts. Thus, the second actin-binding site of CaP (ABS2) and that of UNC-87 are likely to interact with a similar region along the filament.…”
Section: Discussionmentioning
confidence: 81%